KONVERSI KAS DAN DAMPAKNYA TERHADAP LIKUIDITAS DAN PROFITABILITAS DEBITUR USAHA KECIL (Studi Kasus di Bank Sinar Harapan Bali) - Risa Kusumastuti (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
Micro, small, and medium enterprises (SMEs) is an important part of national economy.Despite their advantages, SMEs still often have problems in developing their business and have limited access to capital. In this paper, the author examines the relationship between working capital loan and industry to activity, liquidity, and profitability aspects of small business debtors in Bank Sinar Harapan Bali. The results of this study show that working capital loan and industry influence cash conversion cycle significantly, both simultaneously and partially. Cash conversion cycle affects liquidity and profitability. The total contribution of working capital loan to current ratio through cash conversion cycle variable is amounted 71,05%. The total contribution of industry to current ratio through cash conversion cycle is -14,51%. The total contribution of working capital loan to return on equity through cash conversion cycle variable is amounted 60,48%, while the total contribution of industry to current ratio through cash conversion cycle is -12,35%.